2020
DOI: 10.1101/2020.12.24.424342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell multi-omic analysis identifies aTbx1-dependent multilineage primed population in the murine cardiopharyngeal mesoderm

Abstract: The poles of the heart and branchiomeric muscles of the face and neck are formed from the cardiopharyngeal mesoderm (CPM) within the pharyngeal apparatus. The formation of the cardiac outflow tract and branchiomeric muscles are disrupted in patients with 22q11.2 deletion syndrome (22q11.2DS), due to haploinsufficiency of TBX1, encoding a T-box transcription factor. Here, using single cell RNA-sequencing, we identified a multilineage primed population (MLP) within the CPM, marked by the Tbx1 lineage, which has … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 84 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…Milgrom-Hoffman et al identified Flk1 + /Isl1 + endothelial populations in the second pharyngeal arch in mouse embryos from E7.5 to E9.5 37 . These cell populations may serve as progenitors for LECs and BECs in the cardiopharyngeal region through the sequential expression of Flk1, Tie2 , and/or Prox1 in response to different cues, leading to diverse fate determination, as revealed by recent single cell RNA-sequence analyses 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Milgrom-Hoffman et al identified Flk1 + /Isl1 + endothelial populations in the second pharyngeal arch in mouse embryos from E7.5 to E9.5 37 . These cell populations may serve as progenitors for LECs and BECs in the cardiopharyngeal region through the sequential expression of Flk1, Tie2 , and/or Prox1 in response to different cues, leading to diverse fate determination, as revealed by recent single cell RNA-sequence analyses 38,39 .…”
Section: Discussionmentioning
confidence: 99%